1994
DOI: 10.1007/bf00305522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1-year treatment with ipriflavone on bone in postmenopausal women with low bone mass

Abstract: Ipriflavone (IP) (7-isopropoxyisoflavone), a synthetic isoflavone derivative, is active in both inhibiting bone resorption and enhancing osteoblast function. This property suggested its clinical use in the treatment of involutional osteoporosis, and in the prevention of postmenopausal bone mass loss. Forty postmenopausal women with low bone mineral content were enrolled and randomly treated for 12 months with IP 600 mg/day or placebo (PL), according to a double-blind, parallel group design. All patients wee al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The usual dose in these studies was 600 mg per day, often given in three daily doses of 200 mg. In placebo-controlled studies with a duration of 1 or 2 years, this dose has been shown to inhibit the loss of bone mineral density of the spine (Valente et al, 1994;Agnusdei et al, 1997;de Aloysio et al, 1997;Gambacciani et al, 1997;Gennari et al, 1997) and radius Gennari et al, 1997) that was observed in the control groups. Several studies (Agnusdei et al, 1995;de Aloysio et al, 1997;Gambacciani et al, 1997) have also evaluated the effect of ipri¯avone in combination with low-dose conjugated oestrogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual dose in these studies was 600 mg per day, often given in three daily doses of 200 mg. In placebo-controlled studies with a duration of 1 or 2 years, this dose has been shown to inhibit the loss of bone mineral density of the spine (Valente et al, 1994;Agnusdei et al, 1997;de Aloysio et al, 1997;Gambacciani et al, 1997;Gennari et al, 1997) and radius Gennari et al, 1997) that was observed in the control groups. Several studies (Agnusdei et al, 1995;de Aloysio et al, 1997;Gambacciani et al, 1997) have also evaluated the effect of ipri¯avone in combination with low-dose conjugated oestrogens.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, a number of trials support the preventive effect of ipri¯avone on postmenopausal bone loss Agnusdei et al, 1997;Valente et al, 1994). Ipri¯avone is a synthetic iso¯avone; iso¯avones are natural plant hormones with an oestrogen-like structure, with soy products as their predominant source.…”
Section: Introductionmentioning
confidence: 99%
“…Ipriflavone, (IPR; 7-isopropoxyisoflavone), an isoflavone derivative, has been the phytoestrogen most studied as a therapeutic agent in osteoporosis. Daily oral doses of 3-10 mg/kg/day IPR prevent bone turnover and loss in bone density in women who are postmenopausal or who have been treated with gonadotropinreleasing hormone (GnRH) agonists (132)(133)(134). These doses produce plasma concentrations (135) similar to the in vitro concentrations (≥ 100 nM) required for inhibition of osteoclast differentiation (136) and bone resorption (137).…”
Section: Bone Densitymentioning
confidence: 99%
“…First clinical trials indicate that the compound exerts a beneficial effect in osteopenic diseases [1][2][3]. It is not clear yet whether ipriflavone acts primarily by inhibiting bone resorption or by stimulating bone formation.…”
mentioning
confidence: 99%
“…For measuring bone resorption, we used a technique based on long-term prelabeling with [ 3 H]-tetracycline and the subsequent determination of urinary excretion of the tracer (Fig. 1).…”
mentioning
confidence: 99%